Design optimization and additive manufacturing of nodes in gridshell structures. (1st April 2018) - Seifi, Hamed; Rezaee Javan, Anooshe; Xu, Shanqing; Zhao, Yang; Xie, Yi Min
Highlights: Studied the structural response of new and existing nodes under multiple load cases. The BESO technique reduced the weight and increased the stiffness of node designs. The smoothing algorithm could effectively decrease the maximum stress in the nodes. Abstract: In this paper, two new design approaches are proposed to design structural nodes of complex shapes for gridshell structures, seeking improved structural performance and design efficiency by using the transitional section method and the bi-directional evolutionary structural optimization (BESO) method, respectively. Detailed design methodologies are introduced and compared with two types of conventionally designed structural nodes in real use, i.e., Seele node and Sun Valley node. Finite element analyses are conducted to evaluate the stress distribution, maximum stress and mean compliance of different structural nodes. The results show that, although the BESO node has the highest stiffness and the lowest structural volume, it seems to have a higher maximum stress level. Multiple load cases are considered in the analysis and design optimization processes. Moreover, the application of Laplacian smoothing in structural node design effectively reduces the stress concentration. Prototypes of the newly designed structural nodes are fabricated by additive manufacturing, which enables the rapid and precise manufacturing of customized structural nodes optimized for specific loading and boundary conditions.